Influence of femtosecond laser surface nanotexturing on the friction behavior of silicon sliding against PTFE - Alves-Lopes, Isabel (2019)
The aim of the present work was to investigate the influence of laser-induced periodic surface structures (LIPSS) produced by femtosecond laser on the friction behavior of silicon sliding on polytetrafluoroethylene (PTFE) in unlubricated conditions. Tribological tests were performed on polished and textured samples in air using a ball-on-flat nanotribometer, in order to evaluate the friction coefficient of polished and textured silicon samples, parallel and perpendicularly to the LIPSS orientation. In the polished specimens, the friction coefficient decreases with testing time at 5 mN, while it increases slightly at 25 mN. It also decreases with increasing applied load. For the textured specimens, the friction coefficient tends to decrease with testing time in both sliding directions studied. In the parallel sliding direction, the friction coefficient decreases with increasing load, attaining values similar to those measured for the polished specimen, while it is independent of the applied load in the perpendicular sliding direction, exhibiting values lower than in the two other cases. These results can be explained by variations in the main contributions to friction and in the wear mechanisms. The influence of the temperature increase at the interface and the consequent changes in the crystalline phases of PTFE are also considered.